2019
DOI: 10.1186/s12955-019-1254-2
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the outcomes of long-term care for unpaid carers: comparing the ASCOT-Carer, Carer Experience Scale and EQ-5D-3 L

Abstract: BackgroundThe ASCOT-Carer and Carer Experience Scale are instruments designed to capture aspects of quality of life ‘beyond health’ for family carers. The aim of this study was to compare and validate these two carer care-related measures, with a secondary aim to compare both instruments to the three-level EQ-5D (EQ-5D-3 L) measure of health-related quality of life.MethodsAn interview survey was conducted with 387 carers of adults who used long-term care (also known as social care) support in England. Construc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 14 publications
(36 citation statements)
references
References 43 publications
1
35
0
Order By: Relevance
“…This raises some important considerations around the use of the ASCOT-Carer alongside other generic preference-based health-related quality-of-life measures. Although in a previous study, the ASCOT-Carer showed little overlap with the EQ-5D-3L, 17 some degree of overlap is expected with broader measures of quality of life, such as the ICEpop CAPability measure for Adults or Older Adults, [33][34][35] that requires further investigation. The inclusion of physical and mental health in the CarerQol also creates some challenges around the use of the CarerQol alongside generic measures of health because of the potential risk of double counting.…”
Section: Implications Of Findings and Future Researchmentioning
confidence: 80%
See 2 more Smart Citations
“…This raises some important considerations around the use of the ASCOT-Carer alongside other generic preference-based health-related quality-of-life measures. Although in a previous study, the ASCOT-Carer showed little overlap with the EQ-5D-3L, 17 some degree of overlap is expected with broader measures of quality of life, such as the ICEpop CAPability measure for Adults or Older Adults, [33][34][35] that requires further investigation. The inclusion of physical and mental health in the CarerQol also creates some challenges around the use of the CarerQol alongside generic measures of health because of the potential risk of double counting.…”
Section: Implications Of Findings and Future Researchmentioning
confidence: 80%
“…While previous studies have examined only 1 or 2 of the 3 carer-related preference-based measures within the same study, 14,17 a strength of our study is the exploration of all 3 measures, offering further guidance on the use of the measures in future economic evaluation studies. The inclusion of carers in the online survey, regardless of their age or the condition(s) of the care recipient, represents another strength of our study, making the findings more generalizable to all carers providing informal care.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ASCOT-Carer measures social-care related QoL (SCRQoL) and has emerging evidence of construct validity and feasibility. 20,24 In the United Kingdom, social care refers to community-based services such as home care and day centers, and residential or nursing care. English preference weights have been recently calculated.…”
Section: Introductionmentioning
confidence: 99%
“…7 Informal family caregivers of adults with stroke experience psychological distress and physical burden. 8,9 Therefore, psychological counseling and education for caring skills are provided to those caregivers for the maintenance of their health. 10 An epidemiological study in Japan found that regardless of the degree and type of functional limitation of LTC recipients, their spouses as informal family caregivers experienced a significantly high risk of psychological distress as well as limitations in social participation.…”
Section: Introductionmentioning
confidence: 99%